Desafio do ensino da 1ª lei de Mendel: uma proposta de construção desse conhecimento - André Luiz de Freitas (2020)
Genetics is a branch of Biology focusing on the hereditary. Although the Genetics basis, as Mendel’s first law, for instance, is quite important for a comprehensive education, it is common to have students presenting difficulties on learning it. Thus, this work aimed to create a teaching sequence for High School students on Mendel’s first law and related issues, using inquiring and ludic activities. It was planned to use this teaching sequence on classes, but this was only partially done due the suspension of regular classes during the pandemic time. The teaching sequence has three moments: the first one introduces and contextualizes the subject; the second one is composed by activities on applied situations and related issues; and the third one brings an inquiring activity to teach the occurrence and implications of lethal alleles. The teaching sequence could be partially analyzed regarding the student’s participation during the classes it was used, observed by the teacher/researcher. Several of its aspects were compared with the literature and discussed using the researcher teaching experience. After that, the conclusion was that the developed teaching sequence using ludic and inquiring activities performed in group dynamic can help the teaching-learning process of Mendel’s laws and related issues and increases the student’s participation on learning.